Termination of SUNCT with intravenous lignocaine followed by oral mexiletine - Eoin Mulroy; Oliver Armstrong-Scott; Peter Bergin (SAGE Publishing, 2018)
Background: The trigeminal autonomic cephalalgias (TACs) are a group of debilitating, pathophysiologically similar headache syndromes characterized by facial pain and autonomic symptoms in areas supplied by the trigeminal nerve. Short-lasting unilateral neuralgiform headache with conjunctival injection and tearing (SUNCT) is among the rarest of the TAC syndromes and can be particularly recalcitrant to treatment. Case: We describe the case of a 50-year old woman with difficult-to-control SUNCT whose pain was completely aborted within hours of commencing intravenous lignocaine therapy and was maintained pain-free after transitioning to oral mexiletine. Conclusion: This is the first report of successful transition from intravenous lignocaine to oral mexiletine in SUNCT, and we suggest that this treatment should be tried early in difficult-to-control SUNCT. This therapy is safe, effective and with minimal side effects if administered in an appropriate manner.